CONCEPTUAL METAPHOR A FAMILY IS A HOUSE IN VIETNAMESE - Cuc, Vu Hoang (VNU Journal of Foreign Studies; Vol 36 No 6DO - 10.25073/2525-2445/vnufs.4628, 2020)
The article analyzes the conceptual metaphor A FAMILY IS A HOUSE in Vietnamese to explore the ways Vietnamese people conceptualize family via the domain of HOUSE. To fulfill the research objectives, the article uses the theory of conceptual metaphors and other fundamental concepts of Cognitive linguistics to establish and analyze the mappings from the source domain HOUSE to the target domain FAMILY. The research findings show that Vietnamese people use the house to conceptualize the family as a place to shelter and protect each member. Besides, different parts of the house including the roof, rooftop, pillar, space and the activities of building, destroying the house are also used to express the ways Vietnamese people perceive the roles of the father, husband, family relationships, establishment and breakup and protection of the family. The use of the house to express views of the family demonstrates distinctive cultural features of the Vietnamese people.